Ancient founder mutation is responsible for Imerslund-Gräsbeck Syndrome among diverse ethnicities - Beech Cameron M; Liyanarachchi Sandya; Shah Nidhi P; Sturm Amy C; Sadiq May F; de la Chapelle Albert; Tanner Stephan M (Orphanet Journal of Rare Diseases, 2011)
Abstract Background Imerslund-Gräsbeck syndrome (IGS) was described just over 50 years ago by Olga Imerslund and Ralph Gräsbeck and colleagues. IGS is caused by specific malabsorption of cobalamin (Cbl) due to bi-allelic mutations in either the cubilin gene (CUBN) or the human amnionless homolog (AMN). Mutations in the two genes are commonly seen in founder populations or in societies with a high degree of consanguineous marriages. One particular mutation in AMN, c.208-2A>G, causing an out-of-frame loss of exon 4 in the mRNA, is responsible for some 15% of IGS cases globally. We present evidence that this founder mutation causes a substantial percentage of cases among diverse ethnicities and that the mutation is as old as human civilization. Methods Partial genotyping indicated a founder event but its presence in diverse peoples of Arabic, Turkish, Jewish, and Hispanic ancestry suggested that the mutation might be recurrent. We therefore studied the flanking sequence spanning 3.5 Mb to elucidate the origin of the haplotype and estimate the age of the mutation using a Bayesian inference method based on observed linkage disequilibrium. Results The mutation's distribution, the size of the shared haplotype, and estimates of growth rate and carrier frequency indicated that the mutation was a single prehistoric event. Dating back to the ancient Middle East around 11,600 BC, the mutation predates the advent of writing, farming, and the monotheistic religions of the region. Conclusions This mutation causes over 50% of the IGS cases among Arabic, Turkish, and Sephardic Jewish families, making it a primary target for genetic screening among diverse IGS cases originating from the Middle East. Thus, rare founder mutations may cause a substantial number of cases, even among diverse ethnicities not usually thought to be related.